Mastication muscle activity in boys aged 13-15 years with one-sided chewing habit - Akbar Dwipasya Haliyudha Warokka; Putri Kusuma Wardani Mahendra; Sri Kuswandari (Majalah Kedokteran Gigi Indonesia, 2026)
Unilateral chewing is commonly observed among adolescents aged 13–15 years and may contribute to masticatory muscle imbalance during craniofacial growth. This study aimed to compare masseter and temporalis muscle activity between adolescents with unilateral and bilateral chewing habits. A cross-sectional observational study was conducted, involving 34 male adolescents divided equally into unilateral (n=17) and bilateral chewing groups (n=17). To classify chewing patterns, participants were instructed to chew gum seven times within a 15-second period. Subjects consistently chewing on the same side were categorized as unilateral chewers, whereas those chewing on the same side only four times were classified as bilateral chewers. The dominant side was defined as the side exhibiting greater chewing activity. Surface electromyography (sEMG) was used to measure masseter and temporalis muscle activity during maximal clenching for 5 seconds, repeated three times. Data were analyzed using independent t-tests with a 95% confidence level. In the unilateral chewing group, masseter activity was significantly higher on the dominant side (11.92 ± 1.59 µV) than on the non-dominant side (9.99 ± 1.45 µV) (p < 0.05). Temporalis muscle activity showed a similar pattern (14.21 ± 2.50 µV vs. 12.09 ± 1.42 µV; p < 0.05). No significant side differences were found in the bilateral chewing group (p > 0.05). In conclusion, unilateral chewing in adolescents is associated with increased muscle activity on the dominant side, whereas bilateral chewing demonstrates more balanced masticatory muscle activity.